PENGINTEGRASIAN ILMU-ILMU SOSIAL DENGAN HADIS NABI - Raffi'u, Aliyya Shauma; Faridi, Faridi (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2023)
There are various ways to comprehend the sayings of the Prophet (hadith)and among them are utilizing the approach of asbab al-Wurud (occasions ofrevelation), linguistic approach, and other approaches. Amidst the currentadvancement of knowledge, it is highly feasible to understand the Prophet'shadith through contemporary disciplines such as employing the social sciencesapproach. In this study, the author endeavors to elucidate Prophet's hadith thatcan be understood using a social sciences approach. The method employed in thisresearch is descriptive analysis through a literature review. This study revealsthat understanding the Prophet's hadith through the lens of social sciences isinevitable, given that the sayings of the Prophet are interconnected with specificcontexts, including the psychology of the interlocutors, geographical factors, andothers.